Translational Approaches to Autism Spectrum Disorder - Robinson-Agramonte, Maria de los Angeles.; Robinson-Agramonte, Maria de los Angeles. (Springer International Publishing : Imprint: Springer, 2015)
This book addresses and synthesizes recent basic, translational, and clinical research with the goal of understanding the mechanisms behind autism spectrum disorder (ASD) and how they lead to altered brain function and behavior. Bringing clarity to these mechanisms will lead to more effective therapies for the various heterogeneous pathologies that comprise ASD. Currently there are few, if any, proven therapies for the majority of the disorders. Topics addressed in this book include neural plasticity, neuroimmunology, neuroinflammation, neuroimaging, and appropriate animal and genetic models.